Trend and decomposition analysis of factors influencing teenage pregnancy and motherhood in Nigeria, 2003–2018 - Mobolaji M. Salawu; Rotimi Felix Afolabi; Ayo Stephen Adebowale; Martin Enock Palamuleni (PLoS ONE, 2025)
Background Nigeria is among the countries with a high burden of Teenage Pregnancy and Motherhood (TPM) in sub-Saharan Africa. The adverse effect of TPM on young girls is enormous and often compromises their future socioeconomic advancement, including education. Limited number of studies have assessed the trends in TPM and the decomposition of its contributing factors. This study aimed to assess the levels, trends, and drivers of changes in TPM, between 2003 and 2018, in Nigeria. Methods This study used a cross-sectional design with four consecutive rounds (2003, 2008, 2013, and 2018) of Nigeria Demographic and Health Survey datasets. Women aged 20–49 years who had ever terminated pregnancy, reported at least one childbirth or stillbirth before attaining age 20, were analysed. The outcome variable was having experienced TPM as a teenager. Data were analysed using trend and multivariate decomposition analyses at a 5% significance level. Results The prevalence of TPM was 56.1%, ranging from 64.7% in 2003 to 55.7% in 2018. Overall, the prevalence of TPM decreased significantly by 10.7% over the studied period (p < 0.001). The change was due to a composite of a positive significant effect of the net compositional change (126%) and a negative effect of the net behavioural change (26%). The identified significant drivers of shift in TPM due to changes in the composition of women included current age, educational level, employment status, timing of marriage, age at first sexual intercourse, contraceptive use, ethnicity, and region of residence. Due to the change in behaviour, TPM reduced by 20% among South-South residents compared with their North-Central counterparts. However, TPM increased by 260% among teens who had their first sexual initiation. Conclusions The TPM prevalence remained high in Nigeria, though a decreasing trend was observed within the studied period. Government and other stakeholders should focus pragmatic interventions on the identified drivers of TPM change over the last two decades in their efforts to alleviate TPM in Nigeria.